ACCOUNTING FOR EMPLOYEE STOCK OPTIONS. - Raby, William L. (The Accounting Review, 1962)
Use of employee stock options by large American corporations is widespread. The Courts and the Congress have pondered long and produced complexity in their tax treatment. Financial analysts have been baffled by their possible effects. The accounting profession has once reversed itself as to the effect of issuance of stock options on income, and even yet is far from agreeing that present practice is satisfactory. At least five points of view may be distinguished relative to the accounting aspects of employee stock options: (a) Tax accounting; (b) "Generally accepted" accounting, as reflected by pronouncements of the American Institute of CPAs and the SEC; (c) "Cash value of services" concept; (d) "Accrual of value" concept; (e) Option value concept. This paper initially will look at the effect of the method involved on the reported net earnings of the employer, both in terms of amount and timing. It will then try to set forth a definition of accounting purpose, and test each of the five approaches against that definition. This paper will conclude with its own proposal, based on tax deductions foregone.